CHEMICAL COMPOSITION AND HEALING PROPERTIES (Zingiber officinaie) - Ismoilov Muminjon Yusupovich; Elchiyev Sardorbek Xabibullo o'g'li (Journals Park Publishing, 2023)
This research work is devoted to the extraction of biologically active substances from the medicinal plant ginger (Zingiber officinale), amino acids in extracts and analysis of the results obtained.
Keywords: medicinal plants, ginger, biologically active substance, extract, amino acids, minerals.